Single Suture Synostosis and Isolated Cleft Palate in Non-Apert Syndrome Patients. Issue 2 (March 2019) - Pezas, Theodore; Slator, Rona; White, Nicholas; Lloyd, Mark
Abstract : Introduction: Single suture craniosynostosis (SSC) and isolated cleft palate (ICP) in non-Apert syndrome patients rarely occur together. Management includes airway optimization, timing surgery appropriately, and assessing both cranial vault aesthetics and speech outcomes. The aim of this study was to compare treatment pathways and outcomes in patients with both conditions to standard treatment for these conditions in isolation. Methods: Patient hospital medical records were retrospectively reviewed for demographic data, timing of surgery, aesthetic outcome (using the Whitaker grading system for head shape), and speech outcome (from speech therapy records of general development and speech assessment). Results: Six patients with SSC and ICP were identified over an 18-year period. Cranial surgery was performed between 4 and 16 months and cleft surgery between 6 and 34 months of age in all cases. Documentation of cleft surgery and genetic testing was not available for 1 patient. One patient with hemi-palatal absence had an obturator inserted at 34 months. Two patients were found to have Fragile X and Emanuel syndrome, respectively. No increased perioperative airway risk was highlighted in any case. Four cases were designated Whitaker grade 1, 1 case was designated grade 2, and 1 case was not graded as no cranial surgery was performed. Half of the patients had general and speech developmental delay, while the other half demonstrated no signs of developmental delay. Discussion/Conclusion: Examination of 6 patients with SSC and ICP suggests the presence of both conditions does not adversely impact management or outcome for each condition, or increase perioperative risk.